Acute exacerbation of congestive heart failure following intranasal cocaine use (UCC Student Medical Journal, 2024)
Background: Most presentations of decompensated congestive heart failure occur in patients diagnosed with pre-existing heart failure. Decompensation presents as progressive dyspnea, abdominal and peripheral congestions, as well as neurological symptoms. It typically occurs following physiological stressors such as infection, arrhythmia, or medical non-adherence. Chronic heart failure may result from cardiovascular comorbid conditions, such as coronary artery disease, valvular disease, and long-standing hypertension. Long term cocaine use also results in adverse cardiovascular health. Cocaine use can augment pre-existing risk factors for both chronic congestive heart failure and acute decompensations - namely, coronary artery disease, congestive heart failure, and peripheral vascular disease. It can also independently pose a cardiovascular risk by causing acute ischemia, vasoconstriction, tachycardia, systolic dysfunction, and cardiac remodeling. The Case: the case of a 49-year-old Caucasian male, who presented with worsening dyspnea on exertion and bilateral peripheral edema extending to his abdomen. His symptoms worsened over the preceding week and began after three consecutive days of intranasal cocaine use. He presented with a background history of congestive heart failure, coronary artery disease, peripheral vascular disease, a 30 pack-year smoking history, and weekly cocaine use for the past 12 years. Conclusion: Cocaine use can lead to decompensation of congestive heart failure in patients with extensive cardiac and vascular disease. Cocaine use can also acutely worsen systolic function and cause demand ischemia, on a background of chronic remodelling and atherosclerotic changes. Patient Consent Obtained: Yes
Keywords: CHF